Development of a Technology- Based STEAM Curriculum Model for Improving 21st Century Skills - Satunggale Kurniawan; Ibnu Kanaha (Newinera Publisher, 2026)
This study aims to develop a technology-based STEAM (Science, Technology, Engineering, Arts, and Mathematics) curriculum model to enhance students' 21st-century skills. These skills including creativity, critical thinking, collaboration, and communication are essential in preparing students for the demands of the digital era and global workforce. Using a Research and Development (R&D) approach with the ADDIE (Analyze, Design, Develop, Implement, Evaluate) model, the curriculum was designed, implemented, and evaluated in several high schools in North Halmahera, Indonesia. The results indicate significant improvements: creativity (30%), critical thinking (25%), collaboration (20%), and communication (22%). Students were more engaged and motivated, while teachers reported increased confidence in using educational technology. However, challenges such as time management and technological readiness were noted. Continuous training and curriculum adjustments are needed to optimize implementation. This technology-based STEAM curriculum model offers a practical and innovative approach for future-oriented education. It can serve as a strategic solution for developing holistic competencies aligned with global educational needs and digital transformation.